FACTEURS D’URBANISATION D’UNE ZONE À HAUTE POTENTIALITÉ AGRICOLE54 - Amal Akhdadache; Nasser- Eddine Zine (European Scientific Journal, ESJ, 2014)
The paper presents and analyzes the causes of the transformation of the land use in urban outskirts of Meknes. The City is experiencing a rapid urban growth in a speculative market. It is especially characterized by being crossed by three Wadis: Wadi Boufekrane, Wadi Ouislane and Wadi Bouishak and limited by a strong depression of the land in the North, notwithstanding a substantial proportion of the intensive agricultural area classified by the Master Plan for Urban Planning (SDAU) located in south of Meknes was opened to planning through derogations, due to its soils fertility. 822 hectares of farmland located around the city of Meknes were opened to urbanization via the derogation in urban planning including 312.6 hectares that were very fertile.